Pakistan and the Geopolitics of Supply Routes to Afghanistan - Zahid Anwar (Journal of Political Studies, 2013)
Uneasy lies the head that wears a crown and due to significant geostrategic location of Pakistan its foreign policy, at the out set, remained a tight rope walk for the decision makers at the helm of affairs. This paper explores geostrategic significance of Pakistan in the context of NATO supply routes to Afghanistan. After 9/11 Pakistan became frontline state in the global war against Al-Qaida and its affiliates along the Durand Line. One of the big contributions of Pakistan in this war was its allowing the NATO to use its routes for supply to Afghanistan. Pakistan has provided cheapest and shortest supply routes to NATO forces in Afghanistan. The supply routes through Pakistan are popularly known as Southern Distribution Network while other routes through Russia and Central Asia are called as Northern Distribution Network. No doubt NATO has established alternative routes to Pakistan but they are replete with a host of risks and challenges. NATO efforts are underway to lessen its footprint in Afghanistan and the post 2014 scenario in that landlocked country still lies in smoky cribs. It will be useful to gauge the geostrategic and economic importance of Pakistan by comparing Southern Distribution Network with Northern Distribution Network. If Washington strengthens its relations with Islamabad, Pakistan is the best option with the US for supply and withdrawal of goods from Afghanistan. Weather geostrategic location of a nation state is an asset or a liability depends on the approach of its leadership if the decision makers give priority to national interests the it is an asset otherwise it is like oil, devil`s excrement.